Foreign policy of the Peruvian Revolutionary Government and Changes in the International Order, 1968-1975 - Alcalde Cardoza, Javier (2018)
The Peruvian military government followed between 1968 and 1975 a foreign policy aiming to connect the reforms it pursued internally with reforms proposed by the Group of 77 to the international economic order; it connected also its internal policies with a nationalist current in Latin America that was attempting to restructure the Inter-American System. In doing this, the Peruvian government transformed both the Paradigm and the Grand Strategy of Peruvian foreign policy and presented a challenge to the US hemispheric hegemony. The article explains internal and external conditions that made possible the changes in Peruvian foreign policy and briefly describes the regional and global development of this policy. It explains also how the evolution of some of the aforementioned conditions brought the decline of the revolutionary foreign policy from 1973.